Cardiac amyloid load: a prognostic and predictive biomarker in patients with light-chain amyloidosis - Kristen, Arnt; Siepen, Fabian aus dem; Bauer, Ralf; Hein, Selina; Aurich, Matthias; Riffel, Johannes; Schirmacher, Peter; Katus, Hugo (Journal of the American College of Cardiology, 2016)
Background Cardiac amyloid load has not been analyzed for its effect on mortality in patients with amyloid light-chain (AL) cardiac amyloidosis. Objectives This study retrospectively compared histological amyloid load with common clinical predictors of mortality. Methods This study assessed 216 patients with histologically confirmed cardiac amyloidosis at a single center with electrocardiography, echocardiography, and laboratory testing. Results AL amyloid deposits were usually distributed in a reticular/pericellular pattern, whereas transthyretin amyloid (ATTR) more commonly showed patchy deposits. Median amyloid load was 30.5%; no amyloid load was above 70%. During follow-up (median 19.1 months), 112 patients died. Chemotherapy had a significant effect on overall survival in AL amyloidosis (16.2 months vs. 1.4 months; p = 0.003). Patients with <20% AL amyloid load who responded to chemotherapy showed significantly better survival than nonresponders. According to univariate analysis, predictors of survival in AL amyloidosis included sex, Karnofsky index, New York Heart Association (NYHA) functional class, diastolic blood pressure, estimated glomerular filtration rate, N-terminal pro-B-type natriuretic peptide, mineralocorticoid receptor antagonists, low voltage, ineligibility for chemotherapy, response to chemotherapy, and amyloid load. Independent predictors of mortality by multivariate analysis included NYHA functional class (III vs. II), estimated glomerular filtration rate, responders to chemotherapy, and amyloid load. In ATTR amyloidosis, survival correlated with NYHA functional class, diastolic blood pressure, and use of diuretic agents. Following Cox regression analysis, NYHA functional class (III vs. II; p < 0.05) remained the only independent predictor of patient survival in ATTR amyloidosis. Conclusions Early identification of subjects with AL amyloid is essential given that in late-stage disease with extensive amyloid load, our data suggested that outcomes are not affected by administration of chemotherapy.
Gesehen am 16.01.2019